Japanese fashion designers : the work and influence of Issey Miyake, Yohji Yamamoto and Rei Kawakubo - English, Bonnie (Berg, 2011)
"Over the past 40 years Japanese designers have led the way in aligning fashion with art, ideology and integrity, as well as addressing identity and social politics through dress. They have demonstrated that both creative and commercial enterprise is possible in today's international fashion industry, and have refused to compromise their ideals, remaining autonomous and independent in their design, business affairs and distribution methods. The inspirational Miyake, Yamamoto and Kawakubo have gained worldwide respect and admiration and have influenced a generation of designers and artists alike.Based on twelve years of research, this book provides a richly detailed and uniquely comprehensive view of the work of these three key designers. It outlines their major contributions and the subsequent impact that their work has had upon the next generation of Japanese designers including Watanabe, Takizawa and Takahashi (Undercover), leading Japanese textile designers, and European fashion designers including Margiela and the Belgians, Viktor & Rolf and Chalayan"--Resumé vydavatele
"Reprinted by Bloomsbury Academic 2014, 2015"
Keywords: Miyake, Issey, -- 1938-; Yamamoto, Yōji, -- 1943-; Kawakubo, Rei, -- 1942-; módní návrháři -- Japonsko; módní návrhářky -- Japonsko; módní návrhářství -- Japonsko; fashion designers -- Japan; fashion design -- Japan; studie; studies